2021
DOI: 10.3390/bios11120510
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Flow Immunoassay of SARS-CoV-2 Antigen with SERS-Based Registration: Development and Comparison with Traditional Immunoassays

Abstract: The current COVID-19 pandemic has increased the demand for pathogen detection methods that combine low detection limits with rapid results. Despite the significant progress in methods and devices for nucleic acid amplification, immunochemical methods are still preferred for mass testing without specialized laboratories and highly qualified personnel. The most widely used immunoassays are microplate enzyme-linked immunosorbent assay (ELISA) with photometric detection and lateral flow immunoassay (LFIA) with vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…In this study, the authors confirmed that the sensitivity of SERS-based LFA (100 fg/mL) was seven orders of magnitude higher than that of naked-eye detection (1 μg/mL) for detecting IgM antibodies in a buffer. Similar studies [ 123 , 124 ] have been performed by altering SERS tags or plasmonic nanomaterials, and in all these studies, the sensitivity of SERS-based LFAs was significantly improved compared to that of conventional LFAs.…”
Section: Advanced Technologies In Paper-based Diagnostic Platformmentioning
confidence: 60%
“…In this study, the authors confirmed that the sensitivity of SERS-based LFA (100 fg/mL) was seven orders of magnitude higher than that of naked-eye detection (1 μg/mL) for detecting IgM antibodies in a buffer. Similar studies [ 123 , 124 ] have been performed by altering SERS tags or plasmonic nanomaterials, and in all these studies, the sensitivity of SERS-based LFAs was significantly improved compared to that of conventional LFAs.…”
Section: Advanced Technologies In Paper-based Diagnostic Platformmentioning
confidence: 60%
“…In comparison to the above diagnosis methods, lateral flow immunoassay (LFIA) platforms with optical detection (colorimetry/fluorescence), enzyme-linked immunosorbent assay (ELISA), chemiluminescent immunoassay (CIA), and electrochemistry-based serological test (detection of antibody and antigen) have received much attention for diagnosis COVID-19 (Figure 1b) [13][14][15][16][17]. In particular, electrochemistry-based SARS-CoV-2 virus detection systems have received great potential over 'gold standard' RT-PCR, NA amplification assays, and optical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Surface‐enhanced Raman scattering (SERS)‐based probes have been investigated for both detection and registration of SARS‐CoV‐2 antigen. SERS‐based immunoassays generally do not exhibit matrix effects, enabling direct measurement of antigens without pre‐treatment of biological samples, 41,42 in contrast to conventional fluorescence detection methods 43,44 . Karakus et al 45 reported colorimetric and electrochemical detection of SARS‐CoV‐2 spike protein with gold nanoparticle‐based biosensors to detect as little as 1 pg/ml of the spike protein with linearity over four orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%